THE SCORE OF PROBLEM-THEMATIC COMPLEXES IN I. MCEWAN’S NOVEL “LESSONS” (2022): THE TOPIC OF “THE WAY OF THE HERO” - ДРОЗДОВСЬКИЙ, Дмитро (Київський національний університет імені Тараса Шевченка, 2022)
In the paper, the author explores the problem-thematic landscape explicated in Ian McEwan’s post-postmodern novel “Lessons” (2022). Philosophical aspects of the literary work by the British writer have been studied, in particular, the representation of environmental issues that shape the worldview of the protagonist (Roland). The genre specification of the novel has been clarified, and the genre forms exploited in the novel Lessons have been outlined. Emphasis is placed on the reinforcement of the topics of romantic discourse (with a focus on the metaphysical/transcendental phenomenon represented through music), which is a general typological feature of the British post-postmodern novel. The scope of problem-thematic complexes that define the existential and epistemological landscape of the novel has been determined: the interaction of erotic and thanatological aspects in the life of the protagonist, problems of sexuality, the motif of Roland’s coming of age, awareness of the planetary threat to humanity, the fragility of human life in the second half – end of the 20th century. The specific events in Roland’s life are compared with historical, social and political events, particularly in terms of how the specific and general interact in the space of the novel. Emphasis is placed on the forms of explication of the road motif in McEwan’s Lessons, which involves the sub-motif of self-discovery, rethinking mistakes and self-improvement, etc. In this way, the thematic aspects of the novel reveal the meta-genre pattern of mystery, which opposes the carnivalization of reality in postmodern novels. The protagonist understands the crisis of political institutions and the danger of an ideology that seeks to conquer the individual at all costs. The policy of the USSR indirectly affects the formation of the worldview of the young British man, Roland, giving him the opportunity to accept for the first time his own finitude through the understanding of a hypothetically possible nuclear explosion. The second global problem discussed in the novel as a consequence of the Soviet ideology, is the Chernobyl disaster. The novel reveals the stages of formation of existentially significant categories and values in the life of the protagonist. The detective plot, which revolves around the key intrigue in the novel, intersects with social criticism of power, political discourse in general, environmental policy, etc., combining skepticism and irony with Roland’s attempt to find out the essence of human beings: both physical and metaphysical.

У статті розглядається проблемно-тематичний ландшафт, експлікований у постпостмодерністському романі «Уроки» (2022) Іена Мак’юена. Досліджено філософські аспекти твору британського письменника, зокрема репрезентацію екологічних проблем, що визначають формування світогляду протагоніста (Роланда). З’ясовано жанрову специфікацію твору та окреслено перелік жанрових форм, експлікованих у романі «Уроки». Наголошено на реактуалізації топіки романтичного дискурсу (увага до метафізичного/трансцендентального, представленого за допомогою музики, особливого світогляду), що загалом притаманне британському постпостмодерністському роману. Визначено спектр проблемно-тематичних комплексів, що визначають екзистенційний та епістемологічний ландшафт роману: взаємодія еротичних і танатологічних аспектів у житті протагоніста, проблеми тілесності, мотив дорослішання, усвідомлення планетарної загрози для людства, крихкість людського життя в другій пололовині – наприкінці ХХ ст. Проаналізовано, у який спосіб у романі конкретні події в житті Роланда зіставлено з історичними суспільно-політичними подіями, як конкретне й загальне взаємодіє в художньому просторі роману. Наголошено на формах експлікації мотиву дороги в «Уроках» І. Мак’юена, визначено субмотив самопізнання, переосмислення помилок і самовдосконалення тощо. У такий спосіб окремі змістові блоки роману актуалізують метажанровий патерн містерії, який протистоїть карнавалізації дійсності в постмодерністських романах. Протагоніст розуміє кризу політичних інститутів та небезпеку ідеології, що прагне будь-що підкорити індивіда. Політика СРСР в опосередкований спосіб впливає на формування світогляду британського юнака Роланда, даючи можливість йому вперше усвідомити власну конечність через осмислення гіпотетично можливого ядерного вибуху. Друга глобальна проблема, представлена в романі як наслідок радянської ідеології, – Чорнобильська катастрофа. У творі розкрито етапи формування екзистенційно значущих категорій і цінностей у житті протагоніста: детективний сюжет, якому підпорядкована ключова інтрига в романі, накладається на соціальну критику влади, політичного дискурсу загалом, питань екологічної політики тощо, поєднуючи скепсис, іронію із намаганням Роланда з’ясувати буття людини й людства як тілесного, так і ідеалістично-метафізичного.
ПРОБЛЕМНО-ТЕМАТИЧНІ КОМПЛЕКСИ В РОМАНІ «УРОКИ» (2022) І. МАК’ЮЕНА: ТОПІКА «ШЛЯХУ ГЕРОЯ»
Keywords: постпостмодернізм; сучасний британський роман; Іен Мак’юен; екологічна свідомість; глобальні катастрофи; тілесність; post-postmodernism; contemporary British novel; Ian McEwan; ecological consciousness; global catastrophes; corporeality